Changes to culture pH and dissolved oxygen can enhance chimeric antigen receptor T‐cell generation and differentiation. (8th June 2022) - Lamas, Rodrigo; Ulrey, Robert; Ahuja, Sanjeev; Sargent, Alex
Abstract: Chimeric antigen receptor (CAR) T‐cell therapy is growing clinically and commercially as a powerful new approach to treat cancer. Understanding how key culture conditions such as pH and dissolved oxygen (DO) affect CAR T‐cell generation and function is important in developing better CAR‐T manufacturing processes and CAR T‐cell therapies for patients. We used the automated mini‐bioreactor (AMBR) 15 platform to assess how differences in pH and DO affect CAR T‐cell transduction, proliferation, and differentiation. We found that higher pH can significantly improve CAR T‐cell transduction and proliferation, and also biases CAR T‐cells away from an effector memory and toward a more central memory phenotype. Both high and low DO negatively affect CAR T‐cell generation, with both hypoxic and hyperoxic conditions reducing T‐cell transduction into CAR T‐cells. Collectively, this data underscores how pH and DO can significantly affect CAR T‐cell expansion and differentiation, and provides insight into the optimal culture conditions to enhance CAR T‐cell yield and phenotype in clinical and commercial processes.